Numerical Modelling Of Thermal And Structural Phenomena In Yb:YAG Laser Butt-Welded Steel Elements - Kubiak M.; Piekarska W.; Stano S.; Saternus Z. (Archives of Metallurgy and Materials, 2015)
The numerical model of thermal and structural phenomena is developed for the analysis of Yb:YAG laser welding process with the motion of the liquid material in the welding pool taken into account. Temperature field and melted material velocity field in the fusion zone are obtained from the numerical solution of continuum mechanics equations using Chorin projection method and finite volume method. Phase transformations in solid state are analyzed during heating and cooling using classical models of the kinetics of phase transformations as well as CTA and CCT diagrams for welded steel. The interpolated heat source model is developed in order to reliably reflect the real distribution of Yb:YAG laser power obtained by experimental research on the laser beam profile.